Neural and Behavioral Effects of an Adaptive Online Verbal Working Memory Training in Healthy Middle-Aged Adults - Emch, Mónica; Ripp, Isabelle; Wu, Qiong; Yakushev, Igor; Koch, Kathrin (Frontiers in Aging Neuroscience, 2019)
Neural correlates of working memory training remain a matter of debate, especially in older adults. We used functional magnetic resonance imaging (fMRI) together with an n-back task to measure brain plasticity in healthy middle-aged adults following an 8-week adaptive online verbal working memory training. Participants performed 32 sessions of this training on their personal computers. In addition, we assessed direct effects of the training by applying a verbal working memory task before and after the training. Participants (mean age 55.85 ± 4.24 years) were pseudo-randomly assigned to the experimental group (n=30) or an active control group (n=27). Training resulted in an activity decrease in regions known to be involved in verbal working memory (i.e., fronto-parieto-cerebellar circuitry and subcortical regions), indicating that the brain became potentially more efficient after the training. These activation decreases were associated with a significant performance improvement in the n-back task inside the scanner reflecting considerable practice effects. In addition, there were training-associated direct effects in the additional, external verbal working memory task (i.e., HAWIE-R digit span forward task), indicating that the training generally improved performance in this cognitive domain. These results led us to conclude that even at advanced age cognitive training can improve working memory capacity and increase neural efficiency in specific regions or networks.